WRITING INTRODUCTION SECTIONS OF RESEARCH ARTICLES IN APPLIED LINGUISTICS: CROSS-LINGUISTIC STUDY OF NATIVE AND NON-NATIVE WRITERS - Farnia, Maryam; Barati, Safoora (Indonesian Journal of Applied Linguistics, 2017)
Genre studies allow researchers to observe the repeated communicative functions and their linguistic components in different genres (Brett, 1994). Writing the introduction section is a tough and burdensome task for both native and non-native speakers (Swales Feak, 1994). Hence, the present study aimed to investigate the generic organization of English research article introductions written by native English and Iranian non-native speakers of English. A total of 160 published articles were selected from established journals in Applied Linguistics. Following Swales’ (2004) Create A Research Space (CARS) model, the researchers analyzed the articles for their specific generic patterns. Findings displayed that native English writers used significantly more strategies than Iranian non-native speakers of English, yielding richer texts. The findings of the present study contribute to the current knowledge of cross-cultural studies in academic writing to non-native English speakers in general and to non-native English novice writers in particular. Built on Swales’ (2004) CARS model, the study describes how introduction sections are developed in English by native and non-native speakers, offering insights into ESP/EAP writing pedagogy.